The Buttered Knuckles of the Martial Arts World - A Comprehensive Review on Boxer's Knuckle - Karolina Szala-Czerwonka; Adrian Rejmer; Natalia Woś; Katarzyna Rojek; Lucjan Bednarz; Karolina Wijas; Kinga Bialic; Rafał Bakalarczyk; Artur Bialic; Paweł Majewski (Kazimierz Wielki University, 2023)
Introduction: Boxer's knuckle is a common injury that occurs due to repetitive trauma to the hand, often seen in those who engage in boxing or other similar combat sports. It is a painful condition that can cause swelling, tenderness, and limited movement in the affected area. In some cases, boxer's knuckle can be severe enough to require medical attention and even surgery. This injury can have a significant impact on an athlete's training and overall performance, and it is important to take preventative measures to avoid its occurrence. Understanding the causes, symptoms, and treatment options for boxer's knuckle is essential for any athlete who regularly engages in combat sports or any activity that involves repeated hand trauma. Objective of the study: The objective of this review study is to analyze and summarize the literature related to boxer's knuckle, including its epidemiology, pathophysiology, clinical features, diagnosis, and management. The study aims to provide a comprehensive understanding of the condition, its causes, risk factors, and treatments, and to identify the gaps and limitations in the existing literature. Furthermore, this review intends to provide evidence-based recommendations and guidelines for the prevention, assessment, and treatment of boxer's knuckle in athletes and other individuals who are at risk of developing the condition. Ultimately, the study seeks to contribute to the development of a more precise and effective approach to managing this common hand injury. Material and methods: Review of PubMed articles using the following keywords: "mcp joint rupture boxing", "boxer's knuckle", "metacarpophalangeal joint boxing", "extensor hood injuries". Additionally, related articles proposed by the PubMed website were checked. Single citations that were not in the PubMed database but, in the opinion of the authors, contained valuable knowledge worthy of inclusion in the article were also reviewed.